Does financial asset allocation term structure affect audit fees? Evidence from China - Chuan Zhang; Hongdi Nie (PLoS ONE, 2025)
The financialization of real enterprises presents a dilemma for China’s economic development. This study examines the impact of the financial asset allocation term structure on audit fees using a sample of Chinese A-share listed companies from 2009 to 2019. It also investigates the mediating role of financial risk and the moderating role of independent director characteristics. The results indicate that higher long-term financial assets is associated with higher audit fees, while short-term financial assets show no significant relationship with audit fees. These findings remain robust after several tests. Financial risk mediates the relationship between long-term financial assets and audit fees. Furthermore, among the characteristics of independent directors, the proportion of female independent directors and those with a financial background negatively moderate the relationship between long-term financial assets and audit fees, while independent directors with an overseas background and academic credentials positively moderate this relationship. Additional analysis reveals that firm size and financing constraints exhibit heterogeneity in their effects. This study contributes to the literature by enhancing our understanding of the factors influencing firms’ financial asset allocation and audit fees, and by expanding the literature on the financial risk and characteristics of independent directors.